(untitled) (mathematica didactica, 2005)
Before decimal fractions are taught at the end of grade 6 pupils already gain some experience with decimals, especially in the form of concrete measures. In this process money plays an important role. An empirical investigation in 6 classes of grade 6 students shows how these experiences affect the understanding of abstract decimal fractions.